Peranan Sistem Akuntansi Penerimaan Dan Pengeluaran Kas Dalam Mendukung Pengendalian Internal Kas Pada Badan Keuangan Aset Daerah (BKAD) Provinsi Sumatera Utara - Alyaa Zafira Darmawan; Hendra Harmain; Rahmi Syahriza (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
This research uses a qualitative method with a descriptive approach. The type of data used in this research is primary data, namely interview techniques and secondary data using documentation techniques obtained from the Regional Asset Financing Agency (BKAD) of North Sumatra Province. The results of this research indicate that the accounting system for cash receipts and disbursements at the Regional Asset Financing Agency (BKAD) of North Sumatra Province is classified as good. There are several challenges such as the internet network where not everyone has an internet network, even though the North Sumatra Province Regional Finance and Assets Agency (BKAD) no longer accepts cash payments and now requires them to come directly from the application. However, thanks to daily digital use, the North Sumatra Province Regional Financial and Asset Agency (BKAD) has sufficient cash receipts and expenditures. The Regional Finance and Asset Agency (BKAD) of North Sumatra Province receives and disburses cash as needed.